Systematic evaluation of clinical efficacy of CYP1B1 gene polymorphism in EGFR mutant non-small cell lung cancer observed by medical image - Zhang, Shaofeng; Li, Danqing; Han, Xia (Open life sciences, 2023)
Lung cancer is the cancer with the highest mortality rate and the highest incidence in the world at this stage. Among them, non-small lung cancer is the most common type of lung cancer, and most small cancers have disappeared, which is the optimal time for surgery at the time of diagnosis. To explore and systematically evaluate the clinical efficacy of CYP1B1 gene polymorphism in the treatment of epidermal growth factor receptor (EGFR) Mutant non-small cell lung cancer, this article proposes the principles of lung cancer screening based on CYP1B1 gene polymorphism and polarization imaging and explores the diagnosis and treatment of non-EGFR mutant lung cancer. Based on a large number of medical image data, imageomics can directly reflect the correlation between tumor molecular phenotype and image characteristics by deeply mining some imaging features of the image, which has important value in the early diagnosis of disease, the formulation of personalized treatment plan, and efficacy evaluation and prognosis prediction. A total of 141 NSCLC patients with sensitive EGFR mutation were included in this study, including 101 patients with EGFR single-gene mutation and 40 patients with EGFR multigene mutation coexisting mutation. Both groups of patients were female, aged ≥60 years, no smoking history, no family history of leukemia, adenocarcinoma, lung cancer, stage IV, lymph node metastasis, living, far from metastasis, and ECOG score of 0–2. This study examined the relative number of gene expression and PFS in EGFR multigene co-existing mutations. When the number of mixed genes is 1, 2, and higher, the PFS is 9 months, 8 months, and 6 months, respectively. The PFS time of this group of patients gradually shortened. Therefore, this study examined the benefit of polygenic mutation in estimation by comparing the clinical characteristics of patients with EGFR single-gene mutation and polygenic mutation, to provide measurement of EGFR-TKI and to provide suggestions for future drug selection.